FAKTOR FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN INFRASTRUKTUR - Devina Dharma Putri; Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this study is to find out how the influence of asset structure, profitability, firm size, asset growth, and liquidity has on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The selection of the research sample used the purposive sampling method and the data that matched the criteria were 16 companies. The data processing technique uses multiple regression analysis assisted by the Eviews 12 (Econometric Views) and Microsoft Excel 2019. The results of this study is asset structure, profitability, firm size are significant to capital structure, while assets growth, and liquidity are not significant to the capital structure. The implication of this research is that infrastructure companies need to increase asset growth and liquidity to improve the company's capital structure which will attract investors.